Central tetrahydrobiopterin concentration in neurodevelopmental disorders - Frye, Richard E. (Frontiers in Neuroscience, 2010)
Tetrahydrobiopterin (BH4) is a naturally occurring cofactor essential for critical metabolic pathways. Studies suggest that BH4 supplementation may ameliorate autism symptoms; the biological mechanism for such an effect is unknown. To help understand the relation between central BH4 concentration and systemic metabolism and to develop a biomarker of central BH4 concentration, the relationship between cerebrospinal fluid BH4 concentration and serum amino acids was studied. BH4 concentration was found to be distributed in two groups, a lower and higher BH4 concentration group. Two serum amino acids, citrulline and methionine, differentiated these groups, and the ratio of serum citrulline-to-methionine was found to correlate with the cerebrospinal fluid BH4 concentration (r = -0.67, p < 0.05). Both citrulline and methionine are substrates in inflammation and oxidative stress pathways - two pathways that utilize BH4 and are abnormally activated in autism. These data suggests that central BH4 concentration may be related to systemic inflammation and oxidative stress pathways.